Association between reduced levels of total serum IgE and FcepsilonRI expression in non-releaser basophils - Kumar, P; Singh, B; Lal, R; Rembhotkar, G W; Singh, A B (Immunobiology (1979), 2009)
FcepsilonRI-mediated signal pathway in basophils and mast cells leads to release of histamine and other mediators. Interestingly, basophils from 10% to 20% of the population do not release histamine and other mediators on activation of the IgE signal transduction pathway and this has been attributed to the absence of tyrosine kinases Lyn and Syk. To investigate the association between histamine releasibility, total serum IgE and expression of IgE receptor in releaser and non-releaser phenotypes in Indian population. Basophils from peripheral blood of healthy adults were purified by density gradient centrifugation and negative immuno-selection. Histamine release assay was performed flourometrically. Total serum IgE was estimated by ELISA and assessment of IgE receptor expression was carried out by flow cytometry. Histamine release after ConA challenge varied greatly from 0% to 100% in Indian subjects. Eighteen percent subjects showed less than 5% histamine release (non-releasers). Flow-cytometric analysis revealed a significantly reduced expression of FcepsilonRI in non-releaser basophils (p<0.05). Total serum IgE levels were also significantly low (p<0.05) in non-releasers as compared to releasers. About 18% of the Indian subjects studied showed non-releaser phenotype and also had reduced serum IgE levels and FcepsilonRI expression. As many components like, histamine releasibility, serum IgE and IgE receptors, were found to be reduced in non-releasers, suggesting a common regulators of the phenotype. These needs to be further evaluated and could lead to identification of a potential target for the development of therapeutics for allergic patients.